1982
DOI: 10.1055/s-2007-1002280
|View full text |Cite
|
Sign up to set email alerts
|

Akute virale Enzephalitis mit primär psychotischer Symptomatik - Diagnose, Verlauf und Prognose

Abstract: In 13 cases referred to psychiatric treatment between 1974 and 1980 acute viral encephalitis was diagnosed in the further course of the illness. The majority were female patients. Positive virological or pathological evidence was obtained in 38% of all cases. The most frequent etiology to be found was the herpes-simplex virus. These findings correspond to 36 cases from the literature. 90% of all cases showed neurological symptoms within two weeks of hospital admission. EEG and cerebrospinal fluid examinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

1982
1982
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…An organic paranoid syndrome can only be diagnosed if the psychopathology shows the main diagnostic items and if an organic factor can be found that preceded the syndrome (Lipowski, 1986). Brainin et al (1982) investigated thirteen of their own first admission cases between 1976 and 1980 as well as 36 cases in the literature between 1955 and 1979 concerning an acute viral encephalitis with a primary psychotic symptomatology. Most of the patients (38 out of 49) were given the initial diagnosis of a schizophrenic disorder, mostly catatonic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An organic paranoid syndrome can only be diagnosed if the psychopathology shows the main diagnostic items and if an organic factor can be found that preceded the syndrome (Lipowski, 1986). Brainin et al (1982) investigated thirteen of their own first admission cases between 1976 and 1980 as well as 36 cases in the literature between 1955 and 1979 concerning an acute viral encephalitis with a primary psychotic symptomatology. Most of the patients (38 out of 49) were given the initial diagnosis of a schizophrenic disorder, mostly catatonic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an acute viral meningo-encephalitis can cause psychicdisorders. Brainin et al (1982) found above all acute psychotic symptoms, especially paranoidhallucinatory and catatonic syndromes, in the analysis of their own cases as well as in the review of the literature. Together with the typical neurological findings, eg fever, headache and neck rigidity, it should be easy to establish the connection between the psychiatric symptoms and the underlying organic disease.…”
Section: Introductionmentioning
confidence: 92%
“…This case report suggests a possible association between an unusual pediatric clinical picture and a cerebral HSV reactivation. There are presently no reports on the prevalence and the incidence of such a disease other than isolated case reports mentioned above (3)(4)(5). Considering the fact that a specific antiviral therapy is now available, as well as reports of recurrences of mental symptoms when HSV is reactivated (3), it is essential that the possibility of a HSV infection should be borne in mind and that further investigation with herpes diagnostic tools are used in such acutely confused children.…”
Section: Discussionmentioning
confidence: 99%
“…Älteren klinischen Untersuchungen zufolge gelingt der direkte oder serologische Erregernachweis in 13 % bis 41 % der Patienten mit Virusenzephalitiden (10, 12,47,57,66,98). Im Rahmen einer amerikanischen epidemiologischen Untersuchung wird von einer Erregeridentifikation in 25,7% der im Jahr 1978 gemeldeten Fälle viraler Enzephalitiden berichtet (49).…”
Section: Diskussionunclassified
“…Nur in knapp 30 % unseres Kollektivs wurde die korrekte Diagnose bereits vom einweisenden Arzt formuliert. Ähnliches ist aus älteren Untersuchungen bekannt (4, 12,15,47). Gerade die Frühdiagnose viraler Enzephalitiden ist aber seit der Einführung wirksamer virostatischer Mittel von großer Bedeutung und muß sich auf Ergebnisse zusätzlicher U ntersuchungen stützen (96).…”
Section: Diskussionunclassified